2020
DOI: 10.3390/en13082064
|View full text |Cite
|
Sign up to set email alerts
|

Torrefaction of Straw from Oats and Maize for Use as a Fuel and Additive to Organic Fertilizers—TGA Analysis, Kinetics as Products for Agricultural Purposes

Abstract: This publication presents research work which contains the optimum parameters of the agri-biomass: maize and oat straws torrefaction process. Parameters which are the most important for the torrefaction process and its products are temperature and residence time. Thermogravimetric analysis was performed as well as the torrefaction process using an electrical furnace on a laboratory scale at a temperature between 250-525 • C. These biomass torrefaction process parameters-residence time and temperature-were nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…These results indicate that, as is well known in the production of carbonized solid biofuels, in order to obtain the best process conditions of the torrefaction process and a reasonable price of the final product, it is important to achieve a mass loss on a level of 30% and an energy loss (torgas) on a level of 10% in the thermo-chemical conversion. Compared to research results on other energy crops and straw biomass, Jerusalem artichoke’s temperature of 245 °C during torrefaction for carbonized solid biofuel production under isothermal conditions is relatively low [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Research on the Jerusalem artichoke has shown that the amount of ash after the torrefaction process is still at a relatively low level compared to biomass not subjected to the torrefaction process (Jerusalem artichoke unprocessed as a result of the torrefaction process has an ash content of <3%), and solid fossil fuels, such as Polish hard coal, have an ash content of <15%.…”
Section: Discussionmentioning
confidence: 93%
“…These results indicate that, as is well known in the production of carbonized solid biofuels, in order to obtain the best process conditions of the torrefaction process and a reasonable price of the final product, it is important to achieve a mass loss on a level of 30% and an energy loss (torgas) on a level of 10% in the thermo-chemical conversion. Compared to research results on other energy crops and straw biomass, Jerusalem artichoke’s temperature of 245 °C during torrefaction for carbonized solid biofuel production under isothermal conditions is relatively low [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Research on the Jerusalem artichoke has shown that the amount of ash after the torrefaction process is still at a relatively low level compared to biomass not subjected to the torrefaction process (Jerusalem artichoke unprocessed as a result of the torrefaction process has an ash content of <3%), and solid fossil fuels, such as Polish hard coal, have an ash content of <15%.…”
Section: Discussionmentioning
confidence: 93%
“…49% on the dry basis [ 56 , 57 ], which makes BSG not significantly different in terms of its fuel properties, in comparison to lignocellulosic biomass. Additionally, ash content varies between 2 and 6% [ 57 , 58 , 59 ], which is similar to different types of agricultural biomass [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. However, high moisture content, exceeding 70% [ 56 , 57 ], is a significant obstacle in the use of BSG as a solid biofuel.…”
Section: Thermal Valorization Of Bsgmentioning
confidence: 99%
“…Jewiarz and others have shown that regardless of the tested material (Scots pine, European beech, Giant Miscanthus, and Cup plant) Sokolowski’s grinding criterion G0.25 shows that the energy inputs in the grinding process decrease as the raw material drying temperature increased. Secondly, the authors quantified various parameters of the biomass carbonization process like it was done on different biomass in [ 82 , 83 , 84 ]. These included kinetics, optimal temperature of the biomass roasting process, and residence time for specific mass loss ratios [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%